Nanotubos óxidos aplicados a resinas compostas fotoativadas - Arruda, Larisa Baldo de [UNESP] (2015)
Titanium dioxide (TiO2) has been suggested as a promising material in several applications, especially those solar energy conversion, environmental applications, as photocatalysts, besides being used as biomaterial, mainly because it is a low-cost oxide, chemically stable and by present antibacterial properties. TiO2 nanostructures comes further increasing its field of application, especially when the size of the particles are smaller than 50 nm. The unique photoactivity of TiO2 nanoparticles and their superior mechanical properties when compared to its shape in bulk, makes it ideal as an additive to improve the performance of polymeric materials. In this work, TiO2 nanotubes and nanotubes of TiO2 with different cerium concentrations were obtained by alkaline synthesis followed by successive washes in acide and water, with different final pH values of the solution. The nanotubes obtained were morphologically and structurally characterized and then used as additives in a photopolymerized composite resin, at concentrations of 0.1, 0.3 and 0.6% by weight in order to improve the mechanical properties of hardness and elastic modulus of thet resin and increase the degree of conversion and thereby obtain an improved composite for dental applications. The results show that the show that the synthesized nanotubes, even of different chemical compositions, have an average diameter of 10 nm. It was possibe to identify two differnte growth types for these nanotubes, one from to sheets winding formed during the alkali treatment of starting material and other from to growth of TiO2 single crystals. The difference in final pH values synthesis shown to be an important factor for the determination of the crystal phase obtained, wherein pH values of 4 led to the formation of TiO2 anatase phase only, while pH values exceeding 7 favored the coesistence of TiO2 anatase phase and hydrogen titanate. When incorporated into the resin, the nanotubes acted as a...